Psychological Well-Being of Juvenile Convicts at Class IIA Correctional Institution Sidoarjo - Vivi Widya Susanti; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2013)
The entry of youth into the prisons would lead them to the loss of independence, difficulties in adapting, and lonely feeling, which ultimately affects the condition of psychological well-being. Here, psychological well-being is an essential condition to make teenagers, i.e., convicts, be able to defend their lives for serving a sentence. The study aims to provide an overview of the psychological well-being of juvenile prisoners and to investigate the factors that influence the formation of psychological well-being. In this case, the study employs an exploratory qualitative approach to the subject of two teenage inmates. The prison chosen is located in Class II A Sidoarjo. The data are obtained from interviewing technique and field notes. The results show that inmates have better psychological well-being than when they entered the prison early. The condition is proved at the subjects’ ability to adjust themselves to the environment, develop self-potential, accept themselves in a positive attitude, self-control and self-reliant, have a purpose to live and be able to establish positive relationships with others. Meanwhile, the factors that influence the formation of psychological well-being in inmates are social support, social interaction, and social skills while they are in a prison.